An Ex Vivo Test of Complement Activation on Endothelium for Individualized Eculizumab Therapy in Hemolytic Uremic Syndrome - Galbusera, Miriam; Noris, Marina; Gastoldi, Sara; Bresin, Elena; Mele, Caterina; Breno, Matteo; Cuccarolo, Paola; Alberti, Marta; Valoti, Elisabetta; Piras, Rossella; Donadelli, Roberta; Vivarelli, Marina; et al. (American journal of kidney diseases, 2019)
Although primary atypical hemolytic uremic syndrome (aHUS) is associated with abnormalities in complement genes and antibodies to complement factor H, the role of complement in secondary aHUS remains debatable. We evaluated the usefulness of an ex vivo test to: (1) detect complement activation within the endothelium in primary and secondary aHUS, (2) differentiate active disease from remission, (3) monitor the effectiveness of eculizumab therapy, and (4) identify relapses during eculizumab dosage tapering and after discontinuation of treatment. Case series. 121 patients with primary aHUS and 28 with secondary aHUS. Serum samples were collected during acute episodes, following remission, and during eculizumab treatment and were assessed using a serum-induced ex vivo C5b-9 endothelial deposition test. Serum-induced C5b-9 deposition on cultured microvascular endothelium was quantified by calculating the endothelial area covered by C5b-9 staining; values were expressed as percentage of C5b-9 deposits induced by a serum pool from healthy controls. Testing with adenosine diphosphate–activated endothelium demonstrated elevated C5b-9 deposits for all untreated patients with aHUS independent of disease activity, while testing with unstimulated endothelium demonstrated deposits only in active disease. Similar findings were observed in secondary aHUS. Serum-induced C5b-9 deposits on activated and unstimulated endothelium normalized during eculizumab treatment. 96% (22/23) of patients receiving eculizumab at extended 3- or 4-week dosing intervals demonstrated normal C5b-9 deposits on activated endothelium, despite most patients having CH50Eq (serum complement activity) > 20 UEq/mL, indicating that adequate complement control was achieved even with incomplete blockade of circulating C5. During eculizumab dosage tapering or after treatment discontinuation, all patients experiencing relapses versus only 6% (1/17) of those in stable remission had elevated C5b-9 deposits on unstimulated endothelium. The C5b-9 endothelial deposition test can be performed in only specialized laboratories. Findings on eculizumab dosage tapering need to be confirmed with longitudinal monitoring of C5b-9 deposition. The C5b-9 endothelial deposition assay may represent an advance in our ability to monitor aHUS activity and individualize therapy.